SISTEM AKUNTANSI PENGGAJIAN PADA CV. MAHKOTA SPORT DI SAMARINDA - Danna Solihin, Yuliana Ari H.Eddy Soegiarto (EKONOMIA, 2020)
notes, and report) and collect it tobecome financial information, then report it to easily management in company financial management, the sales system is a component that is paid by the company the employees as a service for the performance that has been given to the company, such compensation is usually given to employess.                                                                        The purpose of this thesis research is to find out and analyze the implementation of the CV. Mahkota Sport accounting sistem.                                                                        The author analysis the payroll system on the CV. Mahkota Sport by using comparing the system applied in the company with the actul system according to the theory and comparing the flow chart attached to the interview process in the form of aquestionnaire which means that according to data by using many answer or interview with part of the related part is accounting for 4 person                                                                        Results analysis mentioning the accounting system at CV. Mahkota Sport is enough according to meed internal control which is supported with questionary results from 16 items questions with score answer yes 75% CV. Mahkota Sport satisfies the elements of a good internal control system. However, there are a number of things that need to be considered, namely in depth examination. Based system implemented by the company has been carried out quite well.